CYTOGENETIC REPORT OF A MALE BREAST-CANCER - Cavalli, L. R.; Rogatto, Silvia Regina [UNESP]; Rainho, C. A.; Dossantos, M. J.; Cavalli, I. J.; Grimaldi, D. M. (Elsevier B.V., 1995)
The cytogenetic findings on G-banding in an infiltrating ductal breast carcinoma in a 69-year-old man are reported. The main abnormalities observed were trisomy of chromosomes 8 and 9 and structural rearrangement in the long arm of chromosome 17 (add(17)(q25)). Our results confirm the trisomy of chromosome 8 in the characterization of the subtype of ductal breast carcinomas and demonstrate that chromosome 17, which is frequently involved in female breast cancers, is also responsible for the development or progression of primary breast cancers in males.